The relationship between compassion fatigue, engagement and decent work among nurses: a cross-sectional study - Yaping Feng; Sui Li; Weilan Ma; Yaqian Chen; Jingxuan Zhang; Hong Luo; Bowen Xue (BMC Nursing)
Abstract Background Nurses face significant professional challenges arising from global pandemics, inadequate welfare protection, and declining social status. In this context, the decent working conditions for nurses are not adequately safeguarded. This study examines decent work status among Chinese nurses and its links work engagement, and compassion fatigue. Methods This study is a cross-sectional research. Through the method of convenience sampling, five reputable hospitals in Hangzhou, China, were selected, and a total of 838 nurses were surveyed. Data collection was conducted from April to May 2023. We employed a comprehensive set of assessment tools, including an evaluation of demographic characteristics, the Decent Work Perception Scale (DWPS), the Chinese version of the Compassion Fatigue Short Scale (C-CFSS), and the Gallup Q12 survey scale. Results The findings of this study demonstrated that compassion fatigue was significantly negatively correlated with both decent work (r = -0.482, p < 0.001) and engagement (r = -0.461, p < 0.001). Additionally, decent work was significantly positively correlated with engagement (r = 0.811, p < 0.001). Mediation analysis revealed that compassion fatigue had a direct negative effect on decent work (β = -0.05, p < 0.001), while engagement partially mediated the relationship between compassion fatigue and decent work (β = -0.14, p < 0.001). Conclusion This study found that compassion fatigue and engagement significantly influence nurses’ perception of decent work, with engagement mediating this relationship. Future research should explore these mechanisms further and develop interventions to enhance engagement and reduce compassion fatigue, improving nurses’ perception of decent work.